2007
DOI: 10.1002/masy.200750215
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spectroscopy in the Optimization and Evaluation of RAFT Agents

Abstract: The selection of a suitable mediating agent in Reversible Addition‐Fragmentation Chain Transfer (RAFT) mediated polymerization is crucial to the degree of control that can be achieved. An overview of work from the Stellenbosch group is presented in which the use of NMR spectroscopy as a tool for evaluating RAFT‐agents is highlighted. The occurrence of selective initialization, i.e. the selective conversion of a RAFT‐agent into its single monomer adduct is discussed for various classes of monomers, as well as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Until recently, little was published on C/LRP of NVP. MADIX polymerization of that monomer follows the same trends than that of VAc: xanthates are particularly suited for the corresponding propagating radicals that are highly reactive, provided the R leaving group is properly selected [28,51,[65][66][67]. The same trend applies for other N-vinyl monomers such as N-vinyl carbazole (N-VCbz) [68].…”
Section: Acrylic Acid and Acrylamido-type Monomersmentioning
confidence: 62%
See 2 more Smart Citations
“…Until recently, little was published on C/LRP of NVP. MADIX polymerization of that monomer follows the same trends than that of VAc: xanthates are particularly suited for the corresponding propagating radicals that are highly reactive, provided the R leaving group is properly selected [28,51,[65][66][67]. The same trend applies for other N-vinyl monomers such as N-vinyl carbazole (N-VCbz) [68].…”
Section: Acrylic Acid and Acrylamido-type Monomersmentioning
confidence: 62%
“…Retention of the dithiocarbonate polymer end groups was demonstrated by chain-extension experiments. In contrast, with R = 2-carboxyethyl (X 18 ) as the leaving group, polymerization of NVP exhibited a 'hybrid behavior', but the same MADIX agent showed fast and selective initialization for VAc, although such a difference was not fully explained [28,66]. As already mentioned, Kamigaito and coworkers reported that xanthates X 2 and X 28 gave well-controlled PNVPs, following inhibition periods of 6 and 1 h, respectively.…”
Section: Acrylic Acid and Acrylamido-type Monomersmentioning
confidence: 89%
See 1 more Smart Citation
“…The past 2 years has seen the publication of further general reviews detailing the RAFT process which include works by Moad, Rizzardo, and Thang, [9][10][11][12] a Handbook of RAFT Polymerization, [13] and a highlight article by Barner-Kowollik and Perrier [14] on the future of RAFT. Reviews on specific areas include the kinetics and mechanism of RAFT polymerization, [15][16][17][18] the use of RAFT to probe the kinetics of radical polymerization, [19,20] the use of RAFT in organic synthesis, [21] amphiphilic block copolymer synthesis, [22,23] the synthesis of end functional polymers, [24] the synthesis of star polymers and other complex architectures, [25,26] the use of trithiocarbonate RAFT agents, [27] the use of xanthate RAFT agents (MADIX), [28] polymerization in heterogeneous media, [29][30][31][32] RAFT polymerization initiated with ionizing radiation, [33] polymer synthesis in aqueous solution, [34][35][36][37] surface and particle modification, [38,39] synthesis of self assembling and/or stimuli responsive polymers, [36,40] RAFT-synthesized polymers in drug delivery, [22,41] and other applications of RAFTsynthesized polymers. [30,42,43] The process is also given substantial coverage in most recent reviews that, in part, relate to polymer synthesis, living or controlled polymerization, or novel architectures.…”
Section: San H Thang Completed His Bsc (Hons) In 1983 and Phd Inmentioning
confidence: 99%
“…[52,53] This controlled radical polymerization technique is based on a twostep addition-fragmentation mechanism using thiocarbonylthio compounds as transfer agents, although the precise mechanism is still under debate. [54,55] For instance, Klumperman et al [56][57][58][59] have investigated the early polymerization behaviour of several RAFT-mediated polymerizations. The period during which the initial RAFT agent was consumed was termed initialization, with different reaction behaviour observed before and after this period.…”
Section: Potential Application To Raft Polymerizationmentioning
confidence: 99%